Decolonize the sociology? Reflections from a practical experience - Philipp Altmann (FahrenHouse, 2020)
The decolonial sociology has been a project of a considerable group of thinkers. There are many texts that contribute to a critique of the colonial and imperial roots of sociology, its questionable institutionalization, its inherent power structures, or its persistent Eurocentrism. However, generally, these texts leave aside the teaching of sociology, especially if it occurs in the Global South. The present text tries to remedy that. It parts from the concrete experience of the formation of a department of social sciences and the reform of the curriculum of sociology in a university of the Global South. This experience and the material related to it form the basis for a theoretical reflection that seeks to bring the decolonial debate into dialogue with a particular local reality. Emphasizing the importance of the local, this text is developed in a scheme that leads to the formulation of three principles for a decolonial sociology: the double contextualization, comparison and self-criticism.